Poultry meat and eggs ? safe to eat? - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2006)
When are poultry and eggs safe to eat, and how should people handle and cook them to eliminate risk of disease transmission?